Coexistence of childhood absence epilepsy and benign epilepsy with centrotemporal spikes: A case series. (May 2017) - Verrotti, Alberto; Casciato, Sara; Spalice, Alberto; Carotenuto, Marco; Striano, Pasquale; Parisi, Pasquale; Zamponi, Nelia; Savasta, Salvatore; Rinaldi, Victoria Elisa; D'Alonzo, Renato; Mecarini, Federico; Ritaccio, Anthony J.; et al.
Abstract: Aim: Childhood absence epilepsy (CAE) and benign childhood epilepsy with centrotemporal spikes (BECTS) are the most common forms of childhood epilepsy. Recent studies in animal models suggest that the two phenotypes may represent a neurobiological continuum. Although the coexistence of CAE and BECTS has been reported, this issue remains controversial. The purpose of this study was to analyse the electro-clinical characteristics of a group of children with contemporary or subsequent features of absence seizures and focal seizures consistent with BECTS. Material and methods: A systematic record review from 8 epilepsy centres was used to identify 11 subjects, 5 females and 6 males, with electro-clinical documented consecutive or contemporary coexistence of CAE and BECTS. Results: Patient's age ranged between 7.8 and 17.3 years. Four out of 11 patients presented concomitant features of both syndromes, whereas the remaining 7 experienced the two syndromes at different times. Conclusions: Although CAE and BECTS are clearly defined syndromes and considered very different in terms of their pathophysiology, they share some features (such as similar age of onset, overall good prognosis), and can occur in the same patient. The long term prognosis of these patients seems to be good with an excellent response to anticonvulsant therapy. Highlights: The coexistence of BECTS and CAE is rare. We report 11 children who showed both types of epilepsy. The patients could present both syndromes concomitantly or at different times. All patients showed an excellent response to anticonvulsant therapy with good long term prognosis.